Pengaruh Hedonic Shopping Motivation, Store Atmosphere dan Shopping Lifestyle Terhadap Impulse Buying pada Makeup Bliss Padang - Siska Mahalia; Lidya Martha (Universitas 45 Surabaya, 2025)
This research aims to test the influence of Hedonic Shopping Motivation, Store Atmosphere and Shopping Lifestyle on Impulse Buying at Makeup Bliss Padang. This type of research is quantitative, where this research uses numerical data and the research process emphasizes objective measurement of results using statistical analysis. The population in this research is Makeup Bliss Padang consumers. However, the number of Makeup Bliss Padang consumers cannot be known for certain and is included in the infinite population category. The sampling technique used was nonprobability sampling and the number of samples was 96 people obtained using the lemeshow formula. The type of data used in this research is quantitative and qualitative data. Meanwhile, the data sources are primary and secondary data sources. The data analysis technique uses multiple linear regression using the SPSS version 21.00 program. The hypothesis was tested using the t test at α = 0.05. The results of this research show that Hedonic Shopping Motivation, Store Atmosphere and Shopping Lifestyle have a positive and significant effect on Impulse Buying at Makeup Bliss Padang.